Exploring a new service prospect: customer' intention determinants in light of utaut theory - Huynh Ngoc Chuong; Vo Tran Phuong Uyen; Nguyen Dang Phuong Ngan; Nguyen Thi Bao Tram; Le Nguyen Bao Tran; Nguyen Thi Thu Ha (Cogent Business & Management, 2024)
Based on the UTAUT theory, this study aims to determine the determinants of customers' intention to use Smart Locker service and specify the relationships between these factors forming on the Resource Matching theory and the Perceived Value theory. The authors applied the SEM model to estimate the primary dataset from 277 potential Ho Chi Minh City customers. This paper showed that there are 8 factors affecting the intention to use Smart Locker of Ho Chi Minh city customers, namely: Convenience (CVN), Privacy Security (PV), Reliability (REL), Functionality (FUN), Service Diversity (SD), Social Influence (SI), Facilitating Conditions (FC), Perceived Value (VAL). The influence of security, service diversity, and social influence on customers' intention to use the Smart Locker is mediated by perceived value `Social Influence' (SI) and it has both direct and indirect impact on the intention to use Smart Locker through `Perceived Value'. The `Perceived Value' (VAL) factor has a significant direct effect, while the `Privacy Security' (PV), and `Service Diversity' (SD) factors have indirect effects on the `Intention to Use' (INT) Smart Lockers. Since then, the authors point out limitations hindering customers' intention to use Smart Locker and offer some solutions for logistics firms to improve their ability to attract customers' intention in Vietnam.
Keywords: 650; smart locker; intention touse; last-mile delivery; seM; new serviceprospect